Análises físico-químicas de polpas de frutas e avaliação dos seus padrões de identidade e qualidade - Fonsêca, Paulinie Adenice Quintiliano da (2012)
The pulps are products that add economic value enjoy the fruits of the surplus productions of the same. Have good market acceptance because of its practicality and diversity of flavors available year round. In order to assess the quality of the fruit pulp through the physical and chemical parameters and the characteristics of manufacturing industry, we analyzed 36 samples of frozen fruit pulp of three brands marketed in RIO Grande do Norte, 14 brand A, 12 of 10 brand B and brand C, which corresponded to 14 different flavors, of which 10 have identity Standards and Quality (ISQ S) established by the Ministério da Agricultura, Pecuária e Abastecimento (MAPA), totaling 27 samples with ISQ s. We conducted the following physicalchemical analyzes on samples of fruit pulp: Total solids, total soluble solids, pH, titratable acidity, total sugars and the determination of ascorbic acid. The percentage of failure for each parameter evaluated was 37, 04% in total soluble solids, 22,22% for total solids and titratable acidity, 7,40% in relation to pH. The total sugars were within the requirements demanded by the MAPA and ascorbic acid content, determined only in the pulp of acerola and cashew, presented a non compliance in the pulp of brand B. The percentage of failures of the pulps with ISQ S was 59% with brand A, B and C accounted for 3,70%, 33,33% and 22,22% respectively. The pulps which have no established atandards such as pineapple pulp, showed similar values between brands and literature data unlike the pulp of plum, jackfruit and tamarind which diverged greatly in parameters such as total solids and total soluble solids. The study demonstrates the need for greater quality control by the producers with respect to raw materials, processing, packing, stored and the importance of ISQ S to establish the flavors have not yet covered by existing legislation, but already highly commercialized